THE EFFECTIVENESS OF STREET VENDOR GUIDANCE PROGRAM BY THE CIVIL SERVICE POLICE UNIT OF GRESIK REGENCY BASED ON GOOD GOVERNANCE PERSPECTIVE - Rohman, Fatqur; Dwijosusilo, Kristyan; Devy Pramudiana, Ika (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the effectiveness of the street vendor (PKL) guidance program by the Civil Service Police Unit (Satpol PP) of Gresik Regency based on good governance perspective and to identify supporting and inhibiting factors of program effectiveness. The research employs a qualitative method with a descriptive approach. Data collection was conducted through in-depth interviews with eight informants consisting of Satpol PP officials, village head, street vendors, and community members. Data analysis used Miles and Huberman's interactive model which includes data reduction, data display, and conclusion drawing. The theoretical framework used is program effectiveness theory from Duncan in Steers (1985) and good governance principles from UNDP (1997). The results show that the effectiveness of the street vendor guidance program is fairly good with target coverage reaching 73.6% and street vendor compliance rate of 60.4%. The implementation of transparency, accountability, responsiveness, and rule of law principles has been running well, however the participation principle still needs improvement. Supporting factors include regulatory support, inter-agency coordination, humanistic approach, and existence of street vendor associations. Inhibiting factors include limited relocation sites, limited resources, suboptimal compliance rates, and limited street vendor participation. The study recommends enhancing street vendor participation in policy formulation and providing more economically viable relocation sites.